Pendekatan Ekonomi Sirkular untuk Pengembangan Bioenergi Berkelanjutan di Komunitas Pertambangan Indonesia - Fadillah, Miftahul; Pratama, Arif Johar; Viendasari, Mila; Nur, Muhammad Syukri (Journal of Empowerment Community, 2026)
The circular economy approach offers a strategic pathway to support sustainability in the mining sector by using local biomass as a renewable energy source. This study examines the potential for implementing a community-based bioenergy system in coal mining areas of South Kalimantan through the integration of biomass availability, community readiness, and reclamation land use. The research methods include a literature review, biomass potential assessment, and a community perception survey using a Likert-scale questionnaire. Three biomass sources were identified—organic waste from worker facilities, reclamation vegetation residues, and wood waste from land clearing—providing an estimated energy potential of 65–972 MWh/year. Energy Plantation Forests (HTE) on reclamation land may further supply 76–203 MWh/ha/year. Survey results indicate strong community support (76–90%) for participation and collective management. The findings highlight that circular bioenergy systems can reduce dependence on LPG/diesel while supporting local MSMEs and employment. Village energy cooperatives are recommended as the primary implementation mode.